Status of Use of Model Drawing Method in Basic level Mathematics Textbook - Acharya, Nara Hari (Journal of Mathematics Education, 2026)
This topic entitled ‘Application of Model drawing Method in Basic level Mathematics Textbook’ is intended to explore the status of the model drawing method in basic-level mathematics textbooks. It is a case study approach in which I have selected the two textbooks grade five and eight published by the government of Nepal, Curriculum Development Center. The model drawing method is a strategy also called the Singapore math strategy to solve mathematical problems by drawing bars in different ways. I found that basic-level mathematics textbooks incorporated model drawing methods to solve problems related to basic operations. Part–part–whole models are more common in a textbook rather than comparison models and parallel bar models. The use of models in arithmetic leads in frequency with comparison to other content areas of the curriculum. The training and workshop for the writer to incorporate model drawings seems necessary for betterment. For proper mathematization and solving different mathematical contextual problems we should develop textbooks form each sector we should incorporate different models of model drawing.